A MONOGRAPHIC REVISION OF RETROPHYLLUM (PODOCARPACEAE). (22nd June 2016) - Mill, R. R.
Abstract : The living species of the genus Retrophyllum C.N. Page (Podocarpaceae) are revised. A key to the six species recognised is given. Retrophyllum filicifolium (N.E.Gray) R.R.Mill comb. nov . from New Guinea and the Moluccas is recognised as a species distinct from R. vitiense (Seemann) C.N. Page, which is restricted to material from Fiji and the Solomon Islands. Additional characters are given by which to separate Retrophyllum piresii (Silba) C.N. Page (Brazil) from R. rospigliosii (Pilg.) C.N. Page (Andes). The six species fall into three species-pairs that differ in reproductive characters: one pair in Papuasia and Melanesia, a second on New Caledonia and a third in South America. In the New Caledonian species-pair, the adult leaves are flattened in four ranks with only minimal heterofacial twisting, whereas in the species-pair inhabiting Fiji, New Guinea and neighbouring areas, as well as the pair inhabiting South America, the adult leaves are arranged in two ranks with significant heterofacial twisting. The names Podocarpus filicifolius N.E.Gray and Nageia minor Carrière, respectively the basionyms of Retrophyllum filicifolium and R. minus, are lectotypified, and the typification of Nageia minor comprehensively discussed in an appendix. Adult female epitypes are additionally designated for Podocarpus filicifolius, which was originally based on juvenile foliage of Retrophyllum mixed with a detached seed of Nageia wallichiana, and for Nageia minor, which Carrière described on the basis of sterile material. Two other appendices provide a list of accepted names and synonyms, and a list of exsiccatae. Illustrations and distribution maps are provided for each species.